Determinants and strategies for environmental compliance in municipalities: Perspectives from KwaZulu-Natal Province, South Africa - Nqobile S. Zungu; Gerhard P. Nortjé (PLoS ONE, 2026)
Background A commitment to local environmental compliance is essential for ensuring a sustainable environment for future generations. Despite South Africa’s extensive environmental laws, municipalities persistently exhibit non-compliance due to inadequate institutional capacity, political interference, and fragmented coordination. Methods This study examines the determinants and strategies influencing environmental compliance in South African municipalities. Utilizing a qualitative research approach and the case study design, 10 municipalities within the KwaZulu-Natal province were sampled, 27 comprehensive interviews were conducted with 16 municipal officials, four environmental consultants (ECs), and seven environmental management inspectors (EMIs). Results The findings suggest that institutional capacity, regulatory enforcement, and political support are crucial determinants of compliance. Furthermore, the study identifies awareness, capacity building, and organisational restructuring as pivotal strategies for enhancing environmental compliance. Conclusions Improving municipal environmental compliance requires stronger leadership commitment, institutional capacity, consistent enforcement, and collaboration. The study contributes to environmental governance and sustainability by elucidating the role of institutional dynamics and political influence in shaping compliance. It provides a foundation for stakeholders, future research, and policy development aimed at effective environmental compliance.